ROE and financial structure of mining companies period 2004-2013 - Acuña Arone, Hector Gil (2019)
According to studies conducted on the international financial crisis of 2008 - 2009,the debate on the “decoupling hypothesis” was reopened. This hypothesis reflectsthe scarce transmission of negative shocks produced by industrialized economiestowards emerging countries. In the collection of studies on decoupling, readings onthe synchronization of the economic cycle between countries are found, with thestudy variable being the GDP. In this investigation we will analyze the US commercialrelationship with respect to Peru with the objective of identifying the dependencyof the real economy with its commercial partner and in this way to be able toprevent future negative external changes. To verify compliance with the decouplinghypothesis, the econometric model is used: rolling analysis being a new model forPeru.